Diversity study of leaf volatile oil constituent of Piper species based on GC/ MS and spatial distribution - Johnson K George, N K Leela, P A Mathew, P Utpala, G R Asish, K V Saji, (Journal of Spices and Aromatic Crops, 2014)
Ten wild Piper species of Western Ghats were studied for leaf volatile oil constituents using GC/MS. The total number of major components (≥ 1%) in different species varied from 5 to 10. The leaf oil was rich in sesquiterpenoids. The most abundant compounds in Piper leaf oil of Western Ghats were β-Caryophyllene, Nerolidol and β - Elemene. Different accessions of P. nigrum collected from different parts of Western Ghats were used to study the spatial diversity of aroma with the help of DIVA GIS. The results indicated that the latitudinal influence was strong in aroma diversity. Total number of components varied from 17 to 73, while the major components found were 10 in P. nigrum leaves. The diversity index of the total component was 2.87.